Desenvolvimento e maturação fisiológica de sementes de pimentão (Capsicum annuum L) - Chartuni Mantovani , Eveline; Ferreira da Silva, Roberto; Dias Casali , Vicente Wagner; Condé, Alcides R (Revista Ceres, 2025)
Studies of the development and physiological maturation of the seeds of sweet pepper (Capsicum annuum L.), cultivar ‘Avelar’, were conducted at Viçosa, Minas Gerais.